Development of Efficient Resource Allocation Techniques for Cooperative Communication Networks using Game Theoretic Models - Lamba, Amanjot Kaur (Thapar University, 2022)
The ever growing need of wireless data services is swiftly saturating channel capacity of present wireless networks. This situation can be dealt with diversity provided by multiple-input multiple-output (MIMO) technology. However, its implementation becomes infeasible for the small size user nodes. Hence, the idea of cooperative communication, which is also regarded as a virtual MIMO, came into existence. With efficient resource allocation, the performance of cooperative systems can be further increased. This research work presents different game theoretic solutions to address the problem of resource allocation in various cooperative networks. First, a novel integrated scheme based on Stackelberg game (SG) and coalitional game (CG) for both disjoint and overlapping coalitions has been implemented in multi-relay environment. This scheme has paid dividend by ensuring an optimal solution, better throughput and fair distribution of payo s among relay nodes. Simulation results have con rmed that the formation of coalitions has yielded comparable system throughput with respect to that of the centralized approach. The difference in system throughput obtained by overlapping coalitions and centralised approach comes out to be a meagre 0.05 Mbps in case of orthogonal multiple access (OMA) and 0.06 Mbps for non-orthogonal multiple access (NOMA). However, for disjoint coalition scheme, it comes out to be 0:09 Mbps and 0:08 Mbps for OMA and NOMA, respectively. Additionally, there is a need to consider the possible uncertainties in the channel parameters known to a user owing to the random and dynamic nature of the wireless medium. A low-complexity robust SG has been presented to investigate the joint problem of relay selection and power allocation in multiple-relay device-to device (D2D) systems in which the imperfect channel state information (CSI) is considered. Optimality of the obtained solution in terms of power and price has been analytically established by proving the existence of the Stackelberg Equilibrium (SE) in the robust game. Effectiveness of the robust game theoretic solution against the nominal solution in terms of system throughput has been confi rmed by the simulation results. Further, a game theoretic solution has been developed based on auction theory for allocating power in downlink multi-user NOMA and hybrid NOMA-OMA networks. The convergence of these games to a unique Nash Equilibrium (NE) has been established mathematically. Simulation results have demonstrated that the average sum rate of users for the auction-based scheme for downlink hybrid NOMA-OMA networks improves by roughly 39.9% and 35.7% of the auction-based scheme for downlink NOMA networks for 3 and 4 pairs of users, respectively. This con rms that in addition to power allocation, user pairing signi cantly improves the performance of NOMA systems. Building upon the above results, a novel cooperative NOMA scheme consisting of low-complexity joint user pairing and subchannel assignment with SG-based power allocation has been proposed. Closed-form expressions for the optimal price set up by the base station (BS) and the power allocated to all users have been derived. The proposed cooperative NOMA scheme yields 25.71% and 45.13% higher average sum rate of users than the random user pairing and xed power allocation (RUP-FPA) cooperative NOMA scheme as well as the cooperative OMA scheme with Pt= 2 = 20 dB and 15 user pairs, respectively. Besides, simulation results have shown that the proposed cooperative NOMA scheme delivers superior performance than the existing NOMA schemes
Keywords: NOMA; Game Theory; Cooperative Communication; Coalition; Power Allocation